# Seventh Grade Math Help?

1) -3s+2(-5s+1) if s = -3

2) -1+9(4d-2)-6d if d = -1

3) 6-2y-6(-3y+7) if y = 3

4) -8(9+2k)+8k+K if K = 6

5) -w-5+5(-5w+9) if w = 1

### 4 Answers

- 7 years agoBest Answer
Hi there --

Two things to keep in mind with these problems -- first, just make sure you follow your order of operations once you substitute; and second, make sure you substitute accurate, watching for transpositions between s and 5, and l and 1, and capitals and lowercase (since they can possibly mean different things when the capital form of the letter stands for one quantity and the lowercase form of the letter stands for another quantity). With that in mind:

1) -3s + 2(-5s + 1); s = -3

. . . . -3(-3) +2(-5∙-3 + 1)

. . . . 9 + 2(15 + 1)

. . . . 9 + 2(16)

. . . . 9 + 32

. . . . 41

2) -1 + 9(4d - 2) - 6d; d = -1

. . . . -1 + 9(4∙-1 - 2) - 6∙-1

. . . . -1 + 9(-4 - 2) - (-6)

. . . . -1 + 9(-6) + 6

. . . . -1 + -54 + 6

. . . . -55 + 6

. . . . -49

3) 6 - 2y - 6(-3y+7); y = 3

6 - 2∙3 - 6(-3∙3 + 7)

. . . . = 6 - 6 - 6(-9 + 7)

. . . . = 6 - 6 - 6(-2)

. . . . = 6 - 6 - (-12)

. . . . = 0 + 12

. . . . = 12

4) -8(9 + 2k) + 8k + k; k = 6

-8(9 + 2∙6) + 8∙6 + 6

. . . . = -8(9 + 12) + 48 + 6

. . . . = -8(21) + 48 + 6

. . . . = -168 + 48 + 6

. . . . = -120 + 6

. . . . = -114

5) -w - 5 + 5(-5w + 9); w = 1

-1 - 5 + 5(-5∙1 + 9)

. . . . = -1 - 5 + 5(-5 + 9)

. . . . = -1 - 5 + 5(4)

. . . . = -1 - 5 + 20

. . . . = -6 + 20

. . . . = 14

I put together a short video tutorial which further illustrates these solutions, and referenced it as a source below. We hope it is helpful.

Source(s): http://www.youtube.com/watch?v=lST9puZKl34 http://www.purplemath.com/modules/evaluate.htm - mr. coolLv 57 years ago
-3s + 2(-5s+1)

-3s + (-10s) + 2

-13s + 2

-13(-3) + 2

39 + 2

41

-1 + 9(4d-2) - 6d

-1 + 36d - 18 - 6d

30d - 19

30(-1) - 19

-30 - 19

-49

6 - 2y - 6(-3y + 7)

6 - 2y - (-18y + 42)

6 - 2y + -1(-18y + 42)

6 - 2y + 18y - 42

16y - 36

16(3) - 36

48 - 36

12

-8(9 + 2k) + 8k + k

-8(2k + 9) + 9k

-16k - 72 + 9k

-7k - 72

-7(6) - 72

-42 - 72

-114

-w - 5 + 5(-5w + 9)

-w - 5 + (-25w) + 45

-26w + 40

-26(1) + 40

-26 + 40

14

- SdeLv 47 years ago
Just put the number into the expression: for example

1)

-3 (-3) + 2 [-5 (-3) + 1] = +9 + 2 (15 + 1) = 9 + 2*16 = 9 + 32 = 41.

So you just need to do the math:)